Implementation of Agricultural Zakat Practices Among Rice Farmers in Rural Bengkulu, Indonesia: A Qualitative Field Study - Bahril, Muthi' 'Adilah; Oktika; Merliana (The Postgraduate of Institut Agama Islam Negeri Metro Lampung, 2025)
Introduction: Agricultural zakat plays an important role in supporting social welfare, yet many rural farmers in Indonesia still lack an understanding of its rules and obligations. In Coko Betung Village, most rice farmers harvest yields that exceed the nishab, but their zakat practices remain informal and guided by tradition rather than Islamic jurisprudence. Objective: This study aims to examine how rice farmers understand, calculate, and implement agricultural zakat, and to identify the factors influencing compliance and non-compliance. Method: Using a qualitative field research approach, data were collected through observations, interviews with 10 purposively selected farmers, and documentation, and were then analyzed using data reduction, data display, and conclusion drawing. Result: The findings show that although most farmers distribute portions of their harvest to neighbors or the local mosque, only a few correctly recognize these acts as obligatory zakat and apply the prescribed rate of 5%–10%. Limited zakat literacy, strong cultural norms, and minimal institutional presence contribute to these gaps. Implication: This suggests the need for targeted zakat literacy programs, enhanced institutional outreach, and community-based strategies to improve agricultural zakat compliance and enhance its socioeconomic impact.